The ultimate guide to sales training : potent tactics to accelerate sales performance - Seidman, Dan (Pfeiffer essential resources for training and HR professionals., 2012)
"The Ultimate Sales Training book enables sales managers, sales trainers, sales coaches, and sales consultants to understand the convergence of selling and learning in the current and future business workplace. The book is a comprehensive tactical, usable, and practical shelf-reference for creating a great sales training program. The book can help those responsible for team performance architect the delicate short-term and long-term balance necessary to create truly world-class sales organizations through training. By focusing on quality, sound instructional design principles, and a standardized sales process, it is sure to be the go-to resource for challenging solving sales training dilemmas"--